IMPLEMENTASI KURIKULUM DALAM MEMANFAATKAN SUMBER BELAJAR SEBAGAI PENUNJANG PEMBELAJARAN - Tria Ayu Wulandari; Hilmi Qosim Mubah (re-JIEM (Research Journal of Islamic Education Management), 2022)
Learning resources are an important part of implementing the curriculum applied to an educational institution, this is because learning resources are able to foster enthusiasm and learning motivation for students and learning resources can help carry out learning activities optimally. The focus of this research is on 3 things, including the use of learning resources to support the implementation of the curriculum, a description of the success of implementing the curriculum as well as the constraints and alternatives. This study uses a descriptive qualitative approach with interviews, observations, and documentation as data collection methods. To determine the validity of the data, the researchers used triangulation of methods and sources so that the degree of validity was higher. The results of this study indicate that optimizing the use of learning resources is very necessary for teachers to achieve curriculum goals, such as the use of messages in stories, teachers as knowledge transfer media, online learning platforms, learning media, learning methods, and learning environments both physically and psychologically. The result of this utilization is that students achieve academic and non-academic achievements. When experiencing obstacles, teachers will immediately take advantage of other sources that are relevant and easily accessible. Teachers are advised to always optimize learning resources so that they are always effective and efficient and always up to date.